THE USE OF SIMULINK BLOCK DIAGRAM TO SOLVE MATHEMATICAL MODELS AND CONTROL EQUATIONS - Ghasem, N. M.; Department of Chemical Engineering University of Malaya, 50603 Kuala Lumpur, Malaysia, School of Engineering, Design and Technology, University of Bradford, Bradford BD7 1DP, UK (2003)
In this paper, the simulink block diagram is used to solve a model consists of a set of ordinary differential and algebraic equations to control the temperature inside a simple stirred tank heater. The flexibility of simulink block diagram gives students a better understanding of the control systems. The simulink alsoallows solution of mathematical models and easy visualization of the system variables. A polyethylene fluidized bed reactor is considered as an industrial example and the effect of the Proportional, Integral and Derivative control policy is presented for comparison.